POTENTIAL SEDIMENT TRANSPORT IN WEIR AEPODU SOUTH KONAWE REGENCY, INDONESIA - Sukri, ahmad Syarif; M, Saripuddin; Karama, Riswal; Nasrul, Nasrul; Talanipa, Romi (Fakultas Teknik Jurusan Sipil Universitas Halu Oleo, 2023)
Land changes and use significantly affected sediment production in the Aepodu watershed, leading to river siltation. The study aims to determine the condition of the Aepodu river flow, and this study is essential to know the potential of sediments that enter the Aepodu weir and the age of the bend. The study uses a qualitative approach with observation and survey methods. The data used in the study included fourteen years of rainfall data, watershed conditions, flow discharge, and sediment observations in the Aepodu weir. The current condition of the Aepodu watershed significantly affects the sedimentation potential judging by the significant potential of expansion sediments of 0.0124m2 / sec, the flow rate of 1,050 m3 / second with large grains that settle at the angle of D75 = 3.5 mm. Potential sidemen in weir Aepudo (QT)= 308,371,965 tons/year, with upstream weir (QV) capacity = 39,375 tons so that the weir is ineffective and must be held sediment dredging.